2D hybrid anode based on SnS nanosheet bonded with graphene to enhance electrochemical performance for lithium-ion batteries1. Issue 58 (25th June 2015) - Li, Shuankui; Zheng, Jiaxin; Zuo, Shiyong; Wu, Zhiguo; Yan, Pengxun; Pan, Feng
<x xml:space="preserve">Abstract</x> A hybrid anode based on SnS nanosheets bonded with reduced graphene oxide (SnS NS/RGO) and synthesized with graphene oxide is formed through a facile solvothermal method.